Functional morphology of the douc langur (Pygathrix spp.) scapula. Issue 6 (3rd March 2017) - Bailey, Katie E.; Lad, Susan E.; Pampush, James D.
Abstract : Most colobine monkeys primarily move through their arboreal environment quadrupedally. Douc langurs ( Pygathrix spp.), however, are regularly observed to use suspensory behaviors at the Endangered Primate Rescue Center (EPRC) in Northern Vietnam. Previous work has linked variation in scapular morphology to different modes of primate arboreal locomotion. Here we investigate whether the shape of the Pygathrix scapula resembles obligate brachiators (gibbons) or obligate arboreal quadrupeds (other cercopithecoids). Using a MicroScribe G2X 3D digitizer, the positions of 17 landmarks were recorded on 15 different species of nonhuman primates ( n = 100) from three categories of locomotor behavior: brachiator, arboreal quadruped, and unknown ( Pygathrix ). All analyses were conducted in the R package geomorph. A Procrustes analysis uniformly scaled the shape data and placed specimens into the same morphospace. A Principal Component Analysis was used to examine scapular shape and a Procrustes ANOVA was conducted to test for shape difference in the scapulae. A pairwise analysis was used to compare the means of the locomotor categories and identify any statistically significant differences. A phylogenetically controlled Procrustes ANOVA was also conducted using a phylogeny from 10kTrees. Results show Pygathrix scapular morphology is significantly different from both arboreal colobine quadrupeds ( p < 0.01) and hylobatid brachiators ( p < 0.01). It does, however, share some features with each including a long vertebral border, like other cercopithecoids, and a more laterally projecting acromion process, like the hylobatids. The principal difference segregating Pygathrix from both the arboreal quadrupeds and the brachiators is the more medially placed superior angle. These nuanced morphological characteristics associated with suspensory behaviors may be useful for inferring suspensory locomotion in the primate fossil record.